2023
DOI: 10.3390/nu15112611
|View full text |Cite
|
Sign up to set email alerts
|

Serum Essential Elements and Survival after Cancer Diagnosis

Abstract: In a prospective study, we measured the associations between three serum elements (Se, Zn and Cu) and the prognosis of 1475 patients with four different types of cancer (breast, prostate, lung and larynx) from University Hospitals in Szczecin, Poland. The elements were measured in serum taken after diagnosis and prior to treatment. Patients were followed from the date of diagnosis until death from any cause or until the last follow-up date (mean years of follow-up: 6.0–9.8 years, according to site). Kaplan–Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Several previously published studies have found a moderate correlation between diminished serum Se levels and survival outcomes in individuals diagnosed with breast and colorectal cancers [ 15 , 16 ]. We also found that high Zn levels correlated with prolonged survival in laryngeal [ 17 ], lung, breast, and prostate cancer patients [ 20 ]. Likewise, low Fe levels can increase the risk of death, as we have shown among a cohort of patients with malignant melanoma and lung cancer [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previously published studies have found a moderate correlation between diminished serum Se levels and survival outcomes in individuals diagnosed with breast and colorectal cancers [ 15 , 16 ]. We also found that high Zn levels correlated with prolonged survival in laryngeal [ 17 ], lung, breast, and prostate cancer patients [ 20 ]. Likewise, low Fe levels can increase the risk of death, as we have shown among a cohort of patients with malignant melanoma and lung cancer [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it forms an integral part of structural and regulatory proteins, including transcription factors, establishing “zinc fingers” that facilitate DNA binding. Zn levels have been linked to survival in prostate, breast, lung, and laryngeal cancers [ 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that cancer patients have elevated copper levels in both their serum and cancer tissue in a multitude of cancers such as oral, ovarian, gastric, breast, renal, thyroid, esophageal, lung, gallbladder, liver, pancreatic, and prostate cancers [5]. In specific cases, such as colorectal and breast cancer, elevated serum copper levels have been associated with cancer staging and progression [119]. Conversely, decreased serum copper levels have been correlated with colorectal and endometrial cancer [5].…”
Section: Copper Serum Levels and Cancermentioning
confidence: 99%
“…ClinChek ®® Serum Control Level I (Recipe, Munich, Germany) was used as a reference material. Detailed information about the analytical procedures were described previously [50].…”
Section: Analytical Proceduresmentioning
confidence: 99%